2021
DOI: 10.1371/journal.pone.0248411
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects analysis of factors associated with health insurance coverage among women in sub-Saharan Africa

Abstract: Introduction In the pursuit of achieving the Sustainable Development Goal targets of universal health coverage and reducing maternal mortality, many countries in sub-Saharan Africa have implemented health insurance policies over the last two decades. Given that there is a paucity of empirical literature at the sub-regional level, we examined the prevalence and factors associated with health insurance coverage among women in in sub-Saharan Africa. Materials and methods We analysed cross-sectional data of 307,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 34 publications
10
46
3
Order By: Relevance
“…This finding was consistent with studies conducted elsewhere. [16][17][18] This is because single women may not afford the premiums, deductibles, and have low perceived illness. According to the current study, participants who engaged in some types of job were positively associated with better coverage of health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding was consistent with studies conducted elsewhere. [16][17][18] This is because single women may not afford the premiums, deductibles, and have low perceived illness. According to the current study, participants who engaged in some types of job were positively associated with better coverage of health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported a direct relationship between maternal age and health insurance coverage. 16,18,19,21 This similarity might be due to the fact that as age increases the risk of getting illness increases; thus, the chance of health insurance coverage will increase. 27 Consistent with previous studies, 16,19,20,22,23 there is a positive relationship between educational status and health insurance coverage among RAG women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations